A digital motion control for the axis movement / Suhaili Yusof @ Arifin - Yusof @ Arifin, Suhaili (1995)
The aim of this work is to control the position of motor rotation that used for the axis movement. Position control performs position moves with no velocity profiling where the user specifies a 24-bit position command from the computer. The controller will remain position locked at a destination that specifies by the user. The system consisting of a Z80 microprocessor unit as the host processor that write a digital information includes address registration and data transfer to the general purpose motion control integrates circuit (1C), HCTL1100. The Z80 assembly language is the software interface loaded in personal computer (PC), which generate the control code and program protocol for control purposes.